Terrorism in Nigeria and Her Neighbours - Oluwaseun Samuel Osadola; Godwin Stephen Emah (Budapest International Research and Critics University, 2022)
Good neighbourliness is no doubt a key policy in managing inter-state relations in the international relations. It developed out of the principles of territorial integrity and sovereignty of states in international law. In recent years, terrorism has become a game of domestic and international politics with implications for peace, security and good governance. Nigeria lies between five francophone countries with geo strategic, identity and security implications. This ipso facto connotes the idea of a split of ethno religious groups originally bounded in historical empires but now exist within the borders of colonially separated states. The recent link and cooperation between the Boko Haram sect and other notorious terrorist groups like Isis (Islamic State of Iraq and the Levant), al Qaeda, and ISWA (Islamic State of West Africa), have internationalized their activities and spread their tentacles into the shores of Nigeria’s neighbouring states like Niger, Cameroon and Chad. This paper argues that terrorism has become a significant setback for global relations and development, considering the good neighbourliness policy which is meant to foster good relationships among states in the international community. This work relies on secondary materials and employs descriptive and analytic methods in analyzing the data for the study.